The effects of influencer marketing on consumers’ purchase intention on beauty products in China - PU, HUIYUN (2022)
Influencer marketing has become more and more important in the company’s marketing communication strategy due to Covid-19. In China, the market size of the influencer economy is huge and continues to rise. Among all industries, the beauty industry tends to depend heavily on influencer marketing to boost transactions because consumers rely heavily on recommendations and referrals when they make purchase decisions on beauty products (Hsu and Ngamnate, 2018). The main research focus of previous studies on influencer marketing lies in the influential factors of its persuasiveness and its impacts on purchase intention. Influencers’ characteristics and para-social interactions between influencers and their followers are the two main topics discussed in the majority of the previous studies. In addition, most of these studies were conducted in European or American regions and focused on social media platforms, such as Facebook and Instagram rather than in the Chinese context. To fill this gap and provide recommendations for Chinese companies and influencers, this research aims at investigating the effects of influencer marketing on consumers' purchase intention on beauty products in China, focusing on Chinese consumers and Chinese social media platforms, like Red, Weibo, Bilibili, etc. To be specific, the individual effect of the 4 attributes (expertise, trustworthiness, attractiveness, and credibility) of social media influencers on consumers' purchase intention on beauty products in China is investigated in this research. 7 variables are developed from the previous research to represent 4 attributes. A research model was developed based on the theoretical framework of source effect, and 4 relevant hypotheses derived from previous research are tested by analysing the primary data which are acquired by sending an online questionnaire. The random sampling method is used and SPSS and Excel are used for analysing data. Overall, 162 valid respondents are recruited. The main findings are: 1/ All four attributes of social media influencers have a positive influence on purchase intention. 2/ Expertise 2 and attractiveness 2 are more influential to purchase intention while trustworthiness is the least influential attribute. 3/ Chinese consumers perceive influencers as good-looking and experienced people in the beauty industry but they are not experts and are hard to be believed. 4/ Purchase intentions do not differ across various demographic groups. Based on the analysis, several implications are offered from both theoretical and managerial perspectives to fill the research gap and provide recommendations to companies and influencers.